Pharmacy Students’ Interpretation of Academic Integrity - Emmerton, Lynne; Jiang, H.; McKauge, L. (American Association of Colleges of Pharmacy, 2014)
Objective: To explore pharmacy students’ recognition and interpretation of situations constituting breaches of academic integrity. Methods: A survey instrument comprising 10 hypothetical student(s) scenarios was completed by 852 students in the bachelor of pharmacy program at an Australian university. The scenarios were relevant to current modes of assessment and presented degrees of ambiguity around academic integrity. Results: Identification of the hypothetical student(s) at fault, particularly in the deliberately ambiguous scenarios, was not related to the respondents’ year of study or sex. Students with fewer years of postsecondary education were more definitive in their interpretation of contentious cases. Respondents from all 4 years of study reported witnessing many of these behaviors among their peers. Conclusion: This study provided novel insight into the ambiguity surrounding academic integrity and students’ perceptions relating to the deliberate or inadvertent involvement of other parties.